Renal Dysfunction among Ghanaians Living with Clinically Diagnosed Hypertension in the Asutifi-South District: A Cross-Sectional Descriptive Study at the St. Elizabeth Hospital, Hwidiem. (5th November 2018) - Lokpo, Sylvester Yao; Osei-Yeboah, James; Owiredu, William K. B. A.; Ussher, Francis Abeku; Orish, Verner Ndudiri; Gadzeto, Felix; Ntiamoah, Paul; Botchway, Felix; Muanah, Ivan; Asumbasiya Aduko, Romeo
Abstract : Background . This study aimed at evaluating the burden of renal dysfunction among people living with hypertension in the Asutifi-South District of the Brong Ahafo Region, who were attending clinic at the St. Elizabeth Hospital in Hwidiem. Methodology . A hospital-based, cross-sectional study was conducted among two hundred (200) hypertensive clients aged between 27 and 88 years who reported for clinical management from January to March, 2018. Data on sociodemography, comorbid disease status, antihypertensive medication, and their duration was obtained using a semistructured questionnaire and patient folders. Blood pressure, weight, and creatinine were measured using standard methods. Kidney function was assessed using Cockcroft Gault (CG), Four-Variable Modification of Diet in Renal Disease (4v-MDRD) and the Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI) equations. The 2012 Kidney Disease Improvement Global Outcome (KDIGO) Criteria were used to categorize renal function among study participants. Results . Renal impairment was observed among 25.00%, 9.50%, and 10.50% of study participants using CG, 4v-MDRD, and CKD-EPI equations, respectively. With the exception of CKD-EPI equation, females significantly recorded higher scores compared to their male counterparts (28.95% vs 12.5%, 11.84%, vs 2.08%) using CG and 4v-MDRD, respectively. Participants aged 50 years or more recorded the highest renal impairment. Conclusion . Renal dysfunction is common among people living with hypertension in the Asutifi-South District of the Brong Ahafo Region. Femininity, older age, disease comorbidity with diabetes, Thiazide diuretic and AR Blocker usage, and increasing duration of medication accounted for higher kidney dysfunction. Regular screening and management are therefore recommended to avert progression to end-stage renal failure (ESRD).